Nurrinaz.co: case study: company analysis / Tengku Nur Akasyah Tuan Soh ... [et al.] - Tuan Soh, Tengku Nur Akasyah; Norzelan, Nurdina Husna; Salim, Intan Zulaikha; Razak, Nurulhuda (2021)
Nurrinaz.Co is a small and medium-sized enterprise (SME) that provides printing pictures and Polaroid services as their main product. This type of printing service is widely famous nowadays among teenagers because they like to save their memory as a picture. Therefore, the demand from the customer is increased and it helps small business like Nurrinaz.Co to gain profit. However, every company will face problems in their business and this includes Nurrinaz.Co, in which we found that there are some major problems that make it difficult for them to improve their business. The problems that Nurrinaz.Co are facing is slow in production, lack of machine and the ineffectiveness of the strategy sales. The first problem is slow in production. The level of production in Nurrinaz.Co is a little bit slow because the business does not have much staff in the production teams as they receive order more than 100 pieces of Polaroid in one day. The second problem that Nurrinaz.Co is facing is lack of machine. It became a problem when they only has one machine printer to fulfil their customer's order. Also, if the machine is damaged or has some problems, they do not have any backup machine to support their business production. The last problem is the ineffectiveness of the strategy sales. Every month Nurrinaz.Co offers a different package for example ‘Baby November Package’ with RM35, ‘Big Deal Package’ with RM25, and ‘Special Package’ with RM40, the differences is only in price but not at their product. It shows that their strategy sales are not too effective in selling their products. Next is the discussion about the solution for every major problems that Nurrinaz.Co faced. There are two solutions for every problem that were stated above. The solution for the slow in production are recruiting new staff and performance support. Firstly, recruiting new staff help to overcome the shortage of qualified workforce. Nurrinaz.Co also should be selective in choosing prospective staff and ensure that they can work quickly, under pressure, on target, and do not refuse to shift work schedules. The advantages in hiring new staff may help the workflow of the production to become more efficient and smooth where it helps in minimizing the workloads on one staff. The disadvantage of this solution is managing a team and creating a positive workplace culture is not easy. Nurrinaz.Co needs to be prepared to deal with staff conflicts, handle tough situations, and have difficulties in conversations. Secondly, performance support, Nurrinaz.Co must be able to provide their staff with practical learning and training to help increase the potentials in their work field skills. The advantage of performance support it helps increase the staff’s productivity. If the staff can access quality support whenever they need it, they can quickly crack on with the task at hand. The performance support disadvantage is the expenses associated with staff training can be daunting for small businesses because the cost is quite expensive. The solution for the second major problem which is lack of machine is by upgrading equipment, and machinery as well as buying new machines. Firstly, upgrade equipment and machinery by implementing regular maintenance, repair, and replacement schedule. The advantage is it will help in speeding the production process and save energy and manpower. The disadvantage is Nurrinaz.Co entirely responsible for the maintenance and repair of the asset, which can be risky if the equipment breaks down or is damaged. Secondly, buying new machines will increase the number of machines in the production process to make as a backup when an unpredictable situation occurs. The advantage is it can facilitate and streamline the production process. While the disadvantage is Nurrinaz.Co needs to spend a lot of their business money to buy a new printer machine. The solution for the last major problem, which is the ineffectiveness of the strategy sales are to give a variety of choices to customers in buying products and creating an alternative. Firstly, give a variety of choices to customers in buying products because customers tend to analyze the attractions of the product rather than the advertising products given to them on social media pictures. The advantage of this solution is by creating a variety of products it is easier for the customer to choose their options quickly. The disadvantage is Nurrinaz.Co will receive many orders and will lead to orders postponing due to a shortage of employees to complete all orders. Secondly, creating an alternative by making catalogue or website for all the products, in which it is easier for the customers to make their own choices and the situation will be more orderly. The advantage is the customers do not need to repeatedly ask the seller about the product available because the catalogue and website is already being provided. The disadvantage is the employees need to constantly update the catalogue and website as soon as they have a new package in their products this will take a lot of time to re-edit the catalogue.